Reconnoitring the past while shaping the future: The identity crisis, internal displacement and the way forward in the Democratic Republic of Congo. Issue 4 (1st October 2020) - Pinduka, Norman; Nhema, Alfred G.
ABSTRACT: The conflict that has embroiled the Democratic Republic of Congo (DRC) for decades has been one of the most vexing problems in the political history of Africa and the larger international community. The grave clashes predominantly in the eastern parts of the country have occasioned various challenges for the state and the world at large, chief among them a record of the internally displaced persons in the state. The forces that have led to internal displacement vary but this paper takes the view that it is a result of the identity crisis, a colonial sarcoma triggered by the arbitrary drawing of borders in the African continent, and in the context of the DRC, forcing 250 different ethnic groups to be embedded in a new state. The paper divulges that the identity crisis is one of the key attributing factors to the unending skirmishes in the DRC, which has led to the escalation of the forcibly displaced people. Without giving attention to such a convoluted historical problem through the establishment of a system based on equality at the national level, the DRC will continuously be infused with unending conflicts which will further precipitate numbers of the forcibly displaced in the country.